2019
DOI: 10.1073/pnas.1907183116
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric structure of an active form of bovine cytochrome c oxidase

Abstract: Cytochrome c oxidase (CcO), a membrane enzyme in the respiratory chain, catalyzes oxygen reduction by coupling electron and proton transfer through the enzyme with a proton pump across the membrane. In all crystals reported to date, bovine CcO exists as a dimer with the same intermonomer contacts, whereas CcOs and related enzymes from prokaryotes exist as monomers. Recent structural analyses of the mitochondrial respiratory supercomplex revealed that CcO monomer associates with complex I and complex III, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 57 publications
(77 reference statements)
2
39
3
Order By: Relevance
“…The identity of these complexes is supported by our proteomic studies, native and denaturing gels, tandem MS experiments, and detergent extraction controls. Since publication, new studies supporting many of our findings have emerged, including studies that show cardiolipin mediating binding between the BAM complex and holotranslocon (14), dimeric ANT-1 in reconstituted membranes (15), E. coli ATP synthase bound to SecYEG (16), and relatively low populations of a complex IV dimer, relative to monomer, in amphipols (17).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The identity of these complexes is supported by our proteomic studies, native and denaturing gels, tandem MS experiments, and detergent extraction controls. Since publication, new studies supporting many of our findings have emerged, including studies that show cardiolipin mediating binding between the BAM complex and holotranslocon (14), dimeric ANT-1 in reconstituted membranes (15), E. coli ATP synthase bound to SecYEG (16), and relatively low populations of a complex IV dimer, relative to monomer, in amphipols (17).…”
supporting
confidence: 53%
“…We acknowledge that ANT-1 can function as a monomer; so can complex V, despite being a dimer. Moreover, a single monomer of complex III is active within a dimer (6); complex IV is functional as both a monomer and a dimer, with the monomer likely the more abundant form (1,17).…”
mentioning
confidence: 99%
“…In their structure, Yang and co-workers found NDUFA4 to be located at the site of Complex IV dimerisation and suggest it and a cardiolipin molecule also present in their structure is displaced by the cholic acid salt used in crystallisation buffers. This conclusion is supported by the work of Shinzawa-Itohet al [41], who recently solved the X-ray structure of both oxidised and reduced forms of bovine Complex IV monomers (at 1.85 Å and 1.95 Å respectively; PDB: 6JY3 and 6JY4) using novel synthetic detergents. Although NDUFA4 is absent from their structures, they found that the activity of Complex IV is lower for the dimer than for the monomer, suggesting the latter to be the active form of the complex [41].…”
Section: Complex Iv: Cytochrome C Oxidasementioning
confidence: 64%
“…In the matrix, Cox5B adopts the same conformation as Cox5A ( Fig. 3), with its Nterminal domain also exhibiting the conformational shift seen compared with the X-ray structure of the bovine ortholog (35,36), which most certainly arises due to the conserved interactions between Cox5 and Cor1 observed with both Cox5 isoforms ( Fig. 3D).…”
Section: Resultsmentioning
confidence: 90%
“…Whether Hig1 type 2 proteins are specific components of those CIVs that form only III-IV SCs remains to be investigated. To date, no evidence of Hig1 proteins or of NDUFA4 has been reported in structural studies of isolated mammalian CIV (35,36), and knockdown of HIG2A in mammalian cells has been shown to cause depletion of all higher-order SCs that contain CIV (27).…”
Section: Discussionmentioning
confidence: 99%